STRATEGIC ALIGNMENT MODEL BETWEEN BUSINESS PROCESSES AND ICT’S THROUGH ENTERPRISE ARCHITECTURES FOR SME’S - Menchaca, Alicia G. Valdez (European Scientific Journal, ESJ, 2014)
Small and Medium manufacturing companies, as a result of globalization, have serious difficulties to compete in international markets, studies show that has been difficult for these businesses to adopt new methods of work organization, that does become more competitive and productive. In Mexico, SME’s have successfully integrated the administrative processes into information and communication technology; moreover the processes of quality and production have less support by ICT’s. This research project proposes a model of strategic alignment between the key business processes of SME’s and the ICT’s, using enterprise architectures. The proposal was applied to a firm of a pilot sample, finding a complete support of management processes by ICT’s. Partial support for production and quality processes, resulting an improvement proposal for the integration of the essential processes of manufacturing SME’s into ICT’s.